1996
DOI: 10.1111/j.1432-1033.1996.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Focal Adhesion Kinase with a 200‐kDa Protein that is Tyrosine Phosphorylated in Response to Platelet‐Derived Growth Factor

Abstract: Focal adhesion kinase (FAK) is a cytoplasmic tyrosine kinase implicated in the signal transduction pathways initiated by integrins. However, we havc previously found that platelet-derived growth factor (PDGF) could stiinulate thc association of FAK with phosphatidylinositol 3-kinase in NIH 3T3 cclls [Chcn, H.-C. & Guan, J.-L. (1994) J, Bid. Chwz. 269, 31 229-31 2331, suggesting that FAK might participate in some of the cellular effects of the growth factors in modulating cell morphology and migration. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In the face of platelet-derived growth factor stimulation, there was a strong association of FAK with pp200 in NIH 3T3 cells. This association was independent of cell adhesion and was therefore thought to be involved with growth factor-induced cellular effects [53]. Sieg et al [54] have also shown that FAK associates with activated PDGF-and EGF-receptors (PDGFR and EGFR) signaling complexes and established that FAK was an important receptorproximal link between growth factor receptor and integrin signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of platelet-derived growth factor stimulation, there was a strong association of FAK with pp200 in NIH 3T3 cells. This association was independent of cell adhesion and was therefore thought to be involved with growth factor-induced cellular effects [53]. Sieg et al [54] have also shown that FAK associates with activated PDGF-and EGF-receptors (PDGFR and EGFR) signaling complexes and established that FAK was an important receptorproximal link between growth factor receptor and integrin signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of hitherto unidentified 190 kDa phosphoproteins in PDGF‐stimulated cells, found by immunoprecipitating with anti‐FAK (Chen and Guan, 1996), anti‐αvβ3 (Bartfeld et al ., 1993) or anti‐caveolin (Liu et al ., 1996) antibodies. In each case, these proteins have been reported not to be reactive with anti‐PDGFβ‐R antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that this p200 is not PDGF-R, but we were not able to identify this protein that should be a cytoskeleton-associated substrate of LMW-PTP. Among proteins that: 1) have a molecular mass of about 200 kDa, 2) reside in the cytoskeleton fraction, and 3) become tyrosine-phosphorylated in response to PDGF, tensin, talin, p190GAP, and a yet unidentified p200 (24) are possible candidates to be a LMW-PTP substrate in the cRIPA fraction.…”
Section: Discussionmentioning
confidence: 99%